3-D reconstruction by extended depth-of-field in tribological analysis: Fractal approach of sliding surface in Polyamide66 with glass fiber reinforcement. (February 2019) - Horovistiz, Ana; Laranjeira, Susana; Davim, J. Paulo
Abstract: The objective of this work was to inspect the fractal behavior of sliding surfaces in Polyamide66 with 30% glass fiber reinforcement. Tribological tests were performed under different conditions and the fractal values were correlated to tribological parameters and evolution of morphological aspects along the surface. Elevation maps of the sliding surfaces were built from images obtained from a conventional optical microscope. Extended depth-of-field method allowed the ordering of stacks of images to quantitative investigation of behavior of surfaces. A robust method to establish the threshold between micro-scale and macro-scales for multi-fractal behavior was proposed, allowing to compare mono-fractal behavior with the ''structural'' (micro scale) and ''textural'' (macro-scale) mixed fractal components. It was found that fractal dimension data were depended on tribological conditions and positions along sliding surfaces.